Isaac H.

asked • 05/23/22

Rewrite the statement ¬∃x (∀y∃tS(x, y, t) ∧ ∃tR(x, t)) so that negations appear only within predicates.

Rewrite the statement ¬∃x (∀y∃tS(x, y, t) ∧ ∃tR(x, t)) so that negations appear only within predicates.

1 Expert Answer

By:

Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.
Most questions answered within 4 hours.

OR

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.